L-arginine impact on inflammatory and cardiac markers in patients undergoing coronary artery bypass graft: a systematic review and meta-analysis of randomized controlled trials - Zahra Mohammadi; Mahdi Ravankhah; Mohammad Ahmadi; Omid Keshavarzian; Isaac Azari; Mozhan Abdollahi; Mehdi Rezaei; Hamed Akbari (BMC Cardiovascular Disorders)
Abstract Background Numerous studies have explored the effects of L-arginine, whether administered in the form of a supplement or through infusion during cardioplegia, on cardiac and inflammatory markers in individuals undergoing coronary artery bypass grafting (CABG). However, these studies presented contradictory findings. Consequently, the objective of this study was to investigate the impact of l-arginine on these markers by analyzing available randomized controlled trials (RCTs). Methods We performed an extensive search across various databases, including Embase, Medline/PubMed, Web of Science, Scopus, Cochrane Library, and Google Scholar, covering research published until December 2023. To analyze the mean changes in inflammatory and cardiac markers between the L-arginine and control groups, we calculated the weighted mean difference (WMD) along with the corresponding 95% confidence interval (CI) using a random-effects model. Results A total of 393 RCTs were identified during the initial search. After screening and selection, 7 trials were included. In a meta-analysis of three trials that reported troponin T levels, we found a significant impact of L-arginine on reducing troponin T levels (WMD = -0.61 ng/ml; 95% CI: -1.07, -0.15). Our analysis also showed that L-arginine had a noticeable impact on decreasing interleukin-6 (IL-6) levels (WMD = -7.72 pg/ml; 95% CI: -15.05, -0.39). However, we found no considerable impact of L-arginine treatment on creatine phosphokinase-MB (CPK-MB), tumor necrosis factor-alpha (TNF-α), and troponin I compared to the placebo groups. Conclusions Our findings suggest that L-arginine may benefit patients undergoing CABG, as it helps reduce inflammatory reactions and limits myocardial ischemia. This study registered in the PROSPERO database (Registration No. CRD42024508341).